Expression of proliferation associated antigens and detection of numerical chromosome aberrations in primary human liver tumours: relevance to tumour characteristics and prognosis. Issue 1 (January 1998) - Nolte, M; Werner, M; Nasarek, A; Bektas, H; von Wasielewski, R; Klempnauer, J; Georgii, A
Abstract : AIMS: To assess cell proliferation and the presence of numerical chromosome aberrations involving chromosomes 1 and 8 in benign and malignant liver tumours. METHODS: Cell proliferation was studied immunohistochemically in paraffin wax embedded material from 62 primary liver tumours (20 hepatocellular carcinomas, 16 cholangiocellular carcinomas, 15 liver cell adenomas, 11 focal nodular hyperplasias), and the results were compared with histological characteristics and clinical data. Copy numbers of chromosomes 1 and 8 were assessed by interphase fluorescence in situ hybridisation (FISH) with satellite probes in fresh tumour material. RESULTS: The expression of proliferation associated antigen Ki67, using the monoclonal antibody MIB-1, and proliferating cell nuclear antigen (PCNA), using the antibody PC10, was found to be significantly higher in malignant versus benign liver tumours. Neither Ki67 nor PCNA expression were independent prognostic parameters. However, there was a tendency for a worse outcome (survival < 12 months) for patients with a high MIB-1 labelling index (> 20%) compared with patients having the same tumour stage and a low MIB-1 index. Aneusomy for chromosomes 1 and 8 was demonstrated by FISH in malignant tumours (six of seven hepatocellular carcinomas, four of five cholangiocellular carcinomas) but not in benign tumours (none of nine) or non-neoplastic liver (none of nine). CONCLUSION: Both the determination of the proliferating cell fraction and FISH analysis are useful for distinguishing hepatocellular carcinoma from liver cell adenoma or focal nodular hyperplasia; high fractions of proliferating cells are predictive of an early relapse.